Lupeol: triterpene from Iraqi Portulaca grandiflora L (Portulacaceae): Its Extraction, identification (GC/MS), Isolation(Combiflash), and Structure Elucidation. - Hadeel Kareem Mus’hib; Thukaa Z. Abdul-jalil (Iraqi Journal of Pharmaceutical Sciences, 2025)
The plant known as Portulaca grandiflora L belongs to the family of flowering plants known as (Portulacaceae). It is a resilient plant that grows well in harsh environments and serves as a traditional remedy in various nations. Eleven O'clock, Moss-rose, Sunplant, gaddi roja, and Neelakeera are just a few of the popular names that are used to refer to this plant across the globe. The primary concern of the present investigation was establishing the presence of lupeol as a new metabolite in the Iraqi Portulaca grandiflora plant, which is triterpenes, have shown significant efficacy as anti-inflammatory, anti-cancer, anti-microbial, cholesterol-lowering, wound healing, and antidiabetic agents. One hundred grams of the entire plant were subjected to a Soxhlet Apparatus (Hot method) to extract lupeol through n-hexane. Two grams of product was the end yield. Lupeol and other phytochemicals have been identified from the normal-hexane part using the GC/MS technique: gas chromatography/mass spectrometry. The process of isolating and purifying lupeol included using Combi-Flash NextGen; hexane extract (0.25 g) and silica gel (4 g) were mixed and then placed into cartilage. After that, it was attached to the combi flash gold column with a solvent mixture that consisted of n-hexane: ethyl acetate (90%:10%) for fraction. The n-hexane fraction is very fruitful due to its abundance of diverse chemicals found in plants belonging to many groups, including fatty acids, volatile oils, phytosterols, triterpenes, aldehyde compounds, terpene alcohols, isomers of vitamin E, diterpenes, alkynes, and alkenes. The melting point, ultraviolet UV spectroscopic, TLC, and Fourier Transform Infrared (FTIR) characteristics of the amorphous powder that was successfully produced showed that it was structurally identical to lupeol. The discovery of Iraqi Portulaca grandiflora as a novel natural source of lupeol opened new horizons toward this promising plant for pharmacological activities and pharmaceutical applications.